Multi-primer target PCR for rapid identification of bovine DRB3 alleles - Ledwidge, S.A.; Mallard, B.A.; Gibson, John P.; Jansen, G.B.; Jiang, Z.H. (Wiley, 2001)
Multi‐primer target polymerase chain reaction (MPT‐PCR) is a rapid method for the identification of specific BoLA‐DRB3 alleles. In a single PCR reaction, the presence of two alleles associated with increased risk, DRB3.2*23 (DRB3*2701–2703, 2705–2707) and decreased risk, DRB3.2*16 (DRB3*1501, 1502), of mastitis in Canadian Holstein can be detected. Two outer primers amplify exon 2 of DRB3. Simultaneously, two inner, allele‐specific primers amplify individual alleles. Initially, 40 cows previously typed by PCR‐restriction fragment length polymorphism (PCR‐RFLP) were genotyped using the multi‐primer approach. An additional 30 cows were first genotyped by multi‐primer target PCR, then by PCR‐RFLP. All animals were correctly identified and there were no false positives. This technique can readily be modified to identify other BoLA alleles of interest.